Principles and Practice of Obstetrics - Padubidri, V. (Oxford University Press, 1999)
This book on obstetrics provides a fundamental knowledge on embryology, and foetal and placental physiology. It emphasizes the importance of antenatal supervision throughout pregnancy and discusses complications and high risk pregnancies. Further, it has sections on normal and abnormal labour and their management, and also on foetal growth and neonatal management. In the present era of 'safe motherhood' and childcare, this book aims to enable practitioners to maintain positive health of pregnant women, leading to the delivery of healthy children, and making the experience of pregnancy and childbirth joyful and gratifying. The procedures and precautions described in this book, if followed, should help in achieving reduced maternal and perinatal mortality. This book is written for M.B.B.S. students, students of Ayurveda studying obstetrics, postgraduate and diploma students of obstetrics and general practitioners